2010
DOI: 10.1007/s00145-010-9084-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Information Analysis: a Comprehensive Study

Abstract: Abstract. Mutual Information Analysis is a generic side-channel distinguisher that has been introduced at CHES 2008. It aims to allow successful attacks requiring minimum assumptions and knowledge of the target device by the adversary. In this paper, we compile recent contributions and applications of MIA in a comprehensive study. From a theoretical point of view, we carefully discuss its statistical properties and relationship with probability density estimation tools. From a practical point of view, we apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(132 citation statements)
references
References 28 publications
1
131
0
Order By: Relevance
“…As expected, and as a straightforward implication of the atomicity principle, the doubling and addition schemes perform exactly the same sequence of field operations if the star (dummy) operations are well chosen 3 . This implies that it is impossible to distinguish a doubling from an addition by just looking at the sequence of calculations (i.e.…”
Section: Attack On Chevallier-mames Et Al's Schemesupporting
confidence: 69%
See 1 more Smart Citation
“…As expected, and as a straightforward implication of the atomicity principle, the doubling and addition schemes perform exactly the same sequence of field operations if the star (dummy) operations are well chosen 3 . This implies that it is impossible to distinguish a doubling from an addition by just looking at the sequence of calculations (i.e.…”
Section: Attack On Chevallier-mames Et Al's Schemesupporting
confidence: 69%
“…Most attacks [3,9,24] enter into this category and the number of different indices i may for instance correspond to the attack order [27]. The second method, called horizontal [13,33], applies on a single algorithm execution.…”
Section: Notations and Basics On Side-channel Attacksmentioning
confidence: 99%
“…We subsequently apply our framework to an example question which is a 'hot topic' in the current literature: Mutual Information Analysis (MIA) was proposed in [11] as an 'optimised' and generic enhancement to correlation-based DPA (CPA), but has disappointed in (most) subsequent comparisons (see [3] for a good overview). By rigorously assessing the theoretic capabilities of MIA with respect to a range of leakage scenarios we shed new light on the rift between the a priori reasoning and the empirical evidence, demonstrating when and in what sense it does represent a superior attack methodology.…”
Section: Our Contributionmentioning
confidence: 99%
“…The authors of [3] presented three such notions and explored how each could be adapted to the purposes of DPA. They subsequently demonstrated that the three were essentially (theoretically) equivalent in the case of a perfectly implemented masking scheme (i.e.…”
mentioning
confidence: 99%
“…This strategy is winning in terms of performance (albeit at the expense of more ROM). Security-wise, as the mask S 1 is no longer uniformly distributed, zero-offset [45] or mutual information attacks [2] become possible. But the degree to which the leakage shall be raised for a CPA attack -on a platform with a linear leakage function -to be successful can be made strictly larger than three (see next section), and thus becomes the relevant security parameter.…”
Section: Multi-mask Fems Vs Mono-mask Lemsmentioning
confidence: 99%